(3GdHhd hGdGSJOdGd Hgs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3aUd fPcQ ajg GdHhd hGdGSJOdGd Hg GdfU(B: (3de UGQ GdHhd EPG deS NGQLkG ef GdMeGe hLO MGQkG s
(3BNQgG (B:s
(3BNQg eHJhQ, jfJgj GdehLhO efg Hbhdg(B: (3GdfU(B: (3GdHhd jOd Ydi Cf GdYdI EeG aj LejY GdHOf HeTGQcI GdYQhb, hEeG aj eLGQj GdHhd NGUI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B149 - (3U(B203s
(3GfXQg eY bhi GdCZPjIs
(3jPcQ fU LGdjfhS Ke ojaSQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B40 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs